Identifikasi Penafsiran Quraish Shihab Tentang Bias Pandangan Ulama terhadap Perempuan: Analisis Hermeneutika Kritis - Kurniasih, Nia; Zulaiha, Eni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Quraish Shihab, an Indonesian Qur'anic exegete, argues that there is a biased perspective towards women rooted in the views of classical scholars and contemporary intellectuals, which, according to him, stems from a misunderstanding of religious texts. Therefore, the aim of this research is to identify Shihab's interpretation of these biases as they relate to specific verses in the Qur'an. Using a qualitative approach and content analysis method, this research is a literature study, with primary data sources being Shihab's thematic exegesis titled Perempuan and Habermas's The Theory of Communicative Action, as well as secondary sources from other relevant literature. The data collection technique employed is documentation, while the data analysis technique utilizes Habermas's critical hermeneutics. The findings reveal that Shihab rejects these biased perspectives. He critiques traditional views by referencing Qur'anic verses and critiques contemporary scholars by correcting their understanding of the verses they cite. Furthermore, based on Habermas's critical hermeneutics analysis, several forms of action and communication are identified in Shihab's interpretation, including normative, communicative, and teleological actions and communication. Criticisms of Shihab's interpretations, as examined through this approach, include several key aspects: an indication of the preservation of patriarchal culture, where some traditional views are upheld; the reinforcement of traditional gender roles, where certain roles are maintained in line with past perspectives; and the limitation of progressive interpretation, which highlights challenges in developing a more contemporary understanding of women's roles in society